A democratic enlightenment the reconciliation image, aesthetic education, possible politics - Schoolman, Morton (Duke University Press, 2020)
"A DEMOCRATIC ENLIGHTENMENT uses the idea of the reconciliation image-developed first by Walt Whitman and expanded in the aesthetic theory of Theodor Adorno-to argue that we are experiencing a new enlightenment moment revolving around the visual aesthetics of film. Political theorist Morton Schoolman argues that films such as The Help and Gentleman's Agreement, which depict violence towards difference (in this case, towards people of color and Jews, respectively) offer a visual image of reconciliation that can serve as a type of aesthetic education, teaching US viewers how to cultivate a democratic sensibility. Schoolman sees this democratic enlightenment as an heir to the earlier European Enlightenment, but expanded beyond Europe. For Schoolman, this new and ongoing democratic enlightenment compels us to revise our conception of enlightenment and how it takes place-not only through language, but also through visual images. The book is divided into three parts: the first focused on Whitman's poetry, the second on Adorno, and the third on the reconciliation image in film. Schoolman first takes up Whitman's 1871 essay Democratic Vistas, which argues that reconciliation is the ideal defining democracy, and that America lacks a cultural aesthetic education to teach this democratic value. According to Schoolman, Whitman seeks to answer this lack with his own poetry, which invokes imagery to teach democratic lessons in a visual form: all-inclusiveness, receptivity, and the imitation of difference. Next, Schoolman traces the concept of aesthetic reason to Adorno and Horkheimer, using their work as the philosophical basis for his claim that aesthetic reason serves as a foundation for the reconciliation image. Instead of understanding the politics of film simply through its narrative structures, Schoolman attends to the aesthetics of two contemporary films to show how they present a complex pedagogy of reconciliation. While some might understand The Help as a white savior narrative, Schoolman argues that the imagery of the movie instead conveys the democratic ideal of reconciling identity and difference. Similarly, while the storyline of Gentleman's Agreement culminates in a narrow politics of tolerance, the imagery of characters negotiating their identity-including presenting as non-Jewish to avoid overt and tacit anti-Semitism in an American suburb-helps us visualize in images of difference the possible politics of becoming different. A DEMOCRATIC ENLIGHTENMENT will interest scholars of literary studies, film, political theory, and critical theory"--